Motor imagery ability in baseball players with throwing yips. - Toshiyuki Aoyama; Kazumichi Ae; Hiroto Soma; Kazuhiro Miyata; Kazuhiro Kajita; Takashi Kawamura (PLoS ONE, 2023)
The motor imagery ability is closely related to an individual's motor performance in sports. However, whether motor imagery ability is diminished in athletes with yips, in whom motor performance is impaired, is unclear. Therefore, this cross-sectional study aimed to determine whether general motor imagery ability or vividness of motor imagery specific to throwing motion is impaired in baseball players with throwing yips. The study enrolled 114 college baseball players. They were classified into three groups: 33 players in the yips group, 26 in the recovered group (previously had yips symptoms but had resolved them), and 55 in the control group. They answered the revised version of the vividness of movement imagery questionnaire (VMIQ-2), which assesses general motor imagery ability. Furthermore, they completed a questionnaire that assesses both positive and negative motor imagery vividness specific to baseball throwing. In the former, they responded to their ability to vividly imagine accurately throwing a controlled ball, whereas in the latter, they responded to the vividness of their experience of negative motor imagery associated with baseball throwing, specifically the image of a wild throw. No significant difference in the VMIQ-2 was found among the three groups. While no significant difference in the vividness of positive motor imagery for ball throwing was found in either first-person visual or kinesthetic perspectives among the three groups, the yips group exhibited significantly higher vividness of negative motor imagery than the control group in both perspectives. These results indicate that negative motor imagery specific to baseball throwing may be associated with symptoms of yips. Therefore, interventions addressing psychological aspects, such as anxiety, which are potential causes of the generation of negative motor imagery, may be necessary to alleviate the symptoms of yips.